2012
DOI: 10.1186/1824-7288-38-74
|View full text |Cite
|
Sign up to set email alerts
|

Clinical application of exhaled nitric oxide measurement in pediatric lung diseases

Abstract: SummaryFractional exhaled nitric oxide (FeNO) is a non invasive method for assessing the inflammatory status of children with airway disease. Different ways to measure FeNO levels are currently available. The possibility of measuring FeNO levels in an office setting even in young children, and the commercial availability of portable devices, support the routine use of FeNO determination in the daily pediatric practice. Although many confounding factors may affect its measurement, FeNO is now widely used in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 157 publications
(138 reference statements)
0
31
0
Order By: Relevance
“…Moreover, the recent availability of hand-held analyzers equipped for nNO measurement, combined with low cost and simple use of the devices, has made nNO determination widespread in primary practice. While fractional exhaled nitric oxide (FeNO) analysis is well validated at any age for measuring airways inflammation, namely in bronchial asthma, [10][11][12][13][14][15][16][17][18] nNO has by far less application in the assessment of pediatric upper airways disorders. Data from studies of nNO measurement in children are relatively scarce except for those supporting its use as screening tool for primary ciliary dyskinesia (PCD).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the recent availability of hand-held analyzers equipped for nNO measurement, combined with low cost and simple use of the devices, has made nNO determination widespread in primary practice. While fractional exhaled nitric oxide (FeNO) analysis is well validated at any age for measuring airways inflammation, namely in bronchial asthma, [10][11][12][13][14][15][16][17][18] nNO has by far less application in the assessment of pediatric upper airways disorders. Data from studies of nNO measurement in children are relatively scarce except for those supporting its use as screening tool for primary ciliary dyskinesia (PCD).…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that common variants in the NO synthesis pathway genes jointly contribute to differences in exhaled nitric oxide (FeNO) levels in children, which is a biomarker of airway inflammation, most likely through differential gene expression [24-26]. In Gravesande et al’ s study, the T allele is associated with lower NO levels, which demonstrates that the Glu298Asp polymorphism is functionally relevant and could be a reason for the low FeNO levels [27].…”
Section: Discussionmentioning
confidence: 99%
“…Respiratory NO production is increased in patients with asthma and allergic rhinitis and exhaled FeNO levels can be used as a marker of lung inflammation in these populations (typically > 25 ppm) [13]. As many of the MD subjects in this study are highly atopic, it would be expected that FeNO levels would be elevated; however, despite their underlying atopic disease, the mitochondrial study subjects demonstrated statistically lower levels of FeNO than the non-atopic age matched controls (Tables 1 and 2).…”
Section: Discussionmentioning
confidence: 99%
“…This level is used as a marker of lung inflammation in patients with asthma, allergic rhinitis, and bronchiectasis to monitor therapy, ie the higher the FeNO level, the higher the inflammation [13]. In contrast, FeNO levels are decreased in several known disease populations including primary pulmonary hypertension, primary cilliary dyskinesia and cystic fibrosis.…”
Section: Introductionmentioning
confidence: 99%